Kinerja rantai pasok PT. X dalam upaya peningkatan keberlanjutan dan responsivitas agroindustri kelapa sawit - Evanila Silvia; Faqih Udin; Tajuddin Bantacut; Marimin Marimin (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
The supply chain of the palm oil agro-industry is quite complicated and lengthy and involves many actors. This causes supply chain performance to be less than optimal. In addition, it also raises doubts applying the principle of sustainability in its business activities. Therefore, it is necessary to evaluate the performance of the supply chain of the palm oil agro-industry to know the actual conditions at the moment and to identify existing problems and opportunities for improvement. Thus, the right strategy can be formulated to increase the sustainability and responsiveness of the palm oil agro-industry. This study aims to identify the condition of the palm oil agro-industry supply chain mechanism and analyze the performance of the palm oil agro-industry supply chain so that improvement strategies can be formulated. Analysis of the supply chain performance of the palm oil agro-industry was determined using the Supply Chain Operation Reference (SCOR) method by weighting the results of the Analytical Hierarchy Process questionnaire (AHP) to obtain the supply chain. The results showed that the supply chain structure of the palm oil agro-industry consisted of farmers, transportation, palm oil mills, private partners, distributors, and consumers. Analysis of the performance of supply chain actors in the palm oil agro-industry is primarily in the medium and above average categories. Improving supply chain performance needs to be emphasized at each stage of the planning process with reliability performance attributes and performance indicators in the form of accuracy in predicting the number of requests. Alternative strategies that are prioritized to improve supply chain performance are increasing the competence of human resources and supply chain partnerships.